Methods Of Teaching Computer Science In Higher Education - Barno Abdullaeva, Khushruya Juraeva,Azamat Kamalov (International Journal of Advanced Science and Technology, 2020)
The article describes effective methods of teaching information communication technologies and their usage in higher education. The features of teaching computer science to students of a technical University with elements of control theory are considered. The importance of taking into account the individual educational trajectory is shown. The use of feedback in training is demonstrated.